Strategic Innovation Model for Business Resilience: A Case Study of PT Zenna Home Living - Hosannah, Matthew Terrence Amadeus; Ratnaningtyas, Sudrajati (PT. EQUATOR SINAR AKADEMIA, 2025)
This research addresses the challenge of sustaining growth in a founder-led SME within the Indonesian home living industry. It focuses on PT Zenna Home Living, a company facing inconsistent growth and operational inefficiencies despite its initial success, indicating a significant gap between its strategic vision and internal capabilities. The primary objective is to diagnose the root causes of this gap and propose a practical model to enhance the company's long-term business resilience. This study employs a qualitative, single case study methodology. Primary data was gathered through in-depth, semi-structured interviews with key informants selected purposefully from three organizational levels—Strategic, Managerial, and Operational. The data was systematically analyzed using thematic analysis, facilitated by NVivo software and guided by the Dynamic Capabilities framework. The results reveal three core strategic gaps: a